The Digitalization of Islamic Practices in Indonesia: A New Era of Religious Expression - David Olumide; Shahril Azman (Artes Libres Institutum, 2025)
The rapid expansion of digital platforms has transformed religious practices worldwide, and Indonesia, with its large Muslim population, provides a unique context for examining these changes. This paper explores how Islamic rituals, religious discourse, and community engagement are being reshaped by digital technology in Indonesia. It investigates the growing role of social media, online preaching, virtual prayer services, and digital religious education in the daily lives of Indonesian Muslims. By employing qualitative research methods, the paper explores the ways in which technology both challenges and enhances traditional forms of religious expression. It also addresses key concerns regarding the authenticity of digital religious practices and the democratization of religious knowledge. The contribution of this research lies in its comprehensive examination of the intersection of religion and technology, offering insights into how the digital age is redefining religious authority, reshaping communal bonds, and facilitating personal expressions of faith. Furthermore, it highlights the role of digital platforms in making Islamic teachings more accessible, especially in remote areas, and in fostering new forms of religious activism. This paper provides a nuanced understanding of the opportunities and challenges posed by the digitalization of religion in Indonesia, contributing to broader discussions on technology, faith, and modernity.